Tolerance Education for Islamic Boarding School Students on Lombok Island - Efendi, Zarkasi; Ansori, Ansori (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
Lombok Island is a small island that is part of the Province of West Nusa Tenggara. In history, Islam on Lombok continues to experience various changes in various aspects including in terms of Islamic boarding schools and religious organizations. It certainly has an impact on the development of religious education in Lombok, where religious education is dominated by a centralized system of Islamic boarding schools. The purpose of this study is to analyze the views of Islamic boarding schools on tolerance education in Lombok and examine the methods and practices of tolerance education for students in Islamic boarding schools in Lombok. This research is a qualitative descriptive study. It explained certain social phenomena. It concludes that the concept of religious tolerance implemented in Islamic boarding schools in Lombok is rahmatan lil 'alamin which in practice always refers to adhering to the principles of ahlusunnah wal jama'ah, such as tawashut (moderate), tawazun (balanced), i'tidal (straight), and tasamuh (tolerance). The methods and practices of instilling the values of religious tolerance in students at Islamic boarding schools are first, organizational education. Second, the study of the turats. Third, the role models of figures or kyai, and the values of tolerance education that are practiced at Islamic boarding schools on Lombok Island are mutual understanding and acceptance, mutual respect and appreciation, deliberation, and upholding equality.